Hopf Bifurcation of a Nonresident Computer Virus Model with Delay (Analysis in Theory and Applications, 2018)
In this paper, a delayed nonresident computer virus model with graded infectionrate is considered in which the following assumption is imposed: latent computershave lower infection ability than infectious computers. With the aid of the bifurcationtheory, sufficient conditions for stability of the infected equilibrium of the modeland existence of the Hopf bifurcation are established. In particular, explicit formulaewhich determine direction and stability of the Hopf bifurcation are derived by meansof the normal form theory and the center manifold reduction for functional differentialequations. Finally, a numerical example is given in order to show the feasibility of theobtained theoretical findings.